2011
DOI: 10.1149/1.3557565
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Cu-Ag Film in Cyanide-Based Electrolyte

Abstract: Electromigration is considered a major concern of the decrease of Cu line reliability. Thus Copper-silver, a promising material for the next generation of interconnect in the aspect of electromigration resistance,has been studied. Electrodeposition in cyanide-based electrolyte was chosen as a Cu-Ag film formation method in this study. To carry out the electrodeposition, a linear sweep voltammetry was conducted to find an optimum reduction potential. Then, the Cu-Ag film was deposited with a static potential me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…[37] Nevertheless, we must consider for comparison that CuÀ Ag electrodeposition from aqueous media often employs metallic and/or Si working electrodes instead of carbon electrodes. [20,37,38] A study using a gas diffusion layer of carbon paper for the electrodeposition of CuÀ Ag from aqueous media exhibited the formation of wireshaped large particles covering the substrate. They observed that the presence of an additive provoked the wires to become porous and thinner, increasing the ECSA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[37] Nevertheless, we must consider for comparison that CuÀ Ag electrodeposition from aqueous media often employs metallic and/or Si working electrodes instead of carbon electrodes. [20,37,38] A study using a gas diffusion layer of carbon paper for the electrodeposition of CuÀ Ag from aqueous media exhibited the formation of wireshaped large particles covering the substrate. They observed that the presence of an additive provoked the wires to become porous and thinner, increasing the ECSA.…”
Section: Resultsmentioning
confidence: 99%
“…Our nanostructures are smaller and better distributed without agglomeration in comparison with the particles obtained in the literature from electrodeposition in aqueous media. Cu−Ag deposits from aqueous media commonly form films covering the whole substrate with agglomerated particles of irregular shape due to faster and uncontrolled deposition kinetics [20,21,37,38] . One of these studies also shows the formation of voids induced by hydrogen embrittlement [37] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations